Pengembangan Konseptual Maharah Kitabah Dalam Pembelajaran Bahasa Arab - Muhammad Miftah Fathurrohman; Ahmad Sobri Maulana; Asep Sopianudin; Rizzaldy Satria Wiwaha; Nurhafizah Nurhafizah (INDO PUBLISHING, 2026)
Arabic language learning often faces major challenges in maharah kitabah (writing skills), which is considered one of the most complex language skills because it requires the integration of linguistic, cognitive, and affective dimensions. Writing is not merely a productive language activity but also a reflection of learners’ language proficiency, as it involves the ability to organize ideas, apply linguistic knowledge, and communicate meaning effectively. Therefore, this study aims to analyze the concept of maharah kitabah development and formulate an integrative and comprehensive framework for Arabic writing instruction. To achieve this objective, the study employs a descriptive qualitative method using a library research approach. Data were collected through a critical review of relevant academic sources, including textbooks, national and international journal articles, and previous studies related to Arabic writing instruction. The collected data were analyzed using content analysis to identify major themes, instructional strategies, and conceptual patterns in the development of maharah kitabah. The findings reveal that the development of writing skills requires systematic, adaptive, and sustainable learning strategies. These strategies include gradual writing practice, contextual learning approaches, the integration of digital technology, the insya’iyah method, and multicultural-based instruction. Furthermore, the study proposes an integrative conceptual model consisting of three stages: introduction, development, and production. The model is designed to facilitate the progressive development of learners’ writing abilities by addressing linguistic, cognitive, and affective needs at each stage. Theoretically, this study contributes an alternative framework for creating more holistic, meaningful, and adaptive Arabic language learning in response to contemporary educational challenges.